Impact of occurrence of cardiac arrest in the donor on long‐term outcomes of pediatric heart transplantation. Issue 12 (8th November 2022) - Sainathan, Sandeep; Said, Sameh; Tsujimoto, Tamy; Lin, Feng‐Chang; Mullinari, Leonardo; Sharma, Mahesh
Abstract: Objective: The impact of cardiac arrest in the donor on long‐term outcomes of pediatric heart transplantation has not been studied. Methods: The UNOS database was queried for primary pediatric heart transplantation (1999–2020). The cohort was divided into recipients who received a cardiac allograft from a donor who had a cardiac arrest (CA) versus a donor who did not (NCA). Univariable and multivariable analysis was done to compare recipient outcomes, followed by survival analysis using the Kaplan–Meier method. Results: A total of 7300 patients underwent heart transplantation, of which 579 (7.9%) patients belonged to the CA group. The CA group was younger (median 3 vs. 5 years, p  < .001), male (51% vs. 47%, p  = .03), and smaller in weight (13 vs. 17 kg, p  < .001) and height (101 vs. 109 cm, p  < .001) than the NCA group. The groups were similar in recipient heart failure diagnosis and blood type. The CA donors were younger (3 vs. 6 years, p  < .001) versus nonwhite (48% vs. 45%, p  = .003) and died from drowning and asphyxiation compared to blunt injury and intracranial hemorrhage in the NCA group. The left‐ventricular ejection fraction was similar between the groups. There was no difference in VAD and ECMO use before the transplant. The listing status, waitlist days, and allograft ischemic times were similar. Posttransplant morbidity such as stroke, dialysis, pacemaker implantation, and treated rejection were similar. Donor cardiac arrest (hazard ratio = 0.93, p  = .5) was not an independent predictor of mortality on multivariable analysis. There was no survival difference even beyond 20 years of follow‐up between the groups ( p  = .88). Conclusion: The occurrence of donor cardiac arrest has no impact on long‐term survival in pediatric heart transplant recipients.